The diversity of saprophytic fungi on agricultural land in Wukirsari, Cangkringan, Sleman, Yogyakarta - Siti Umniyatie; Victoria Henuhili (Jurnal Sains Dasar, 2014)
This research aims to 1) examine the total amount of fungi, 2) the diversity of top soil saprophytic soil fungus, and 3) the abiotic soil factor that is believed to influence the diversity of fungi genus in the village of Wukirsari, Cangkringan, Sleman, Yogyakarta. This is an exploration research using the soil from agricultural land in the village of Wukirsari, Cangkringan, Sleman, Yogyakarta as sample through stratified random sampling. Sample is taken from the top soil in zone A, B, and C. The total amount of fungi are obtained using the pour plate method by dilution technique up to 10-8 , while edaphic factors are determine through soil tester. The measurement of soil organic C is using Walked and Black method while as for N total and P total using Kyeldal and HCL 25%, respectively. Soil fungus identification is conducted by identifying microscopic and macroscopic characteristics and subsequently the results are compared to Compendium of Soil Fungi. This research shows that there are variations of the amount and genus of fungi found in the sample. Zone B has the highest total of fungi, 35 x 105 cfu/gram while zone A and C has 14 x 105 cfu/gram and 2.4 x 105 cfu/gram, respectively. There are 24 isolate fungi that belong to 10 genus, namely: Penicellium sp., Humicola sp, Mucor sp, Fusarium sp, Acromonium sp Cochliobolus sp, Botrytis sp. and Mycothecium sp.. Zone B has the same diversity with zone A, and zone C has lower diversity. The diversity is determined by the soil edaphic, in particular humidity. While the content of organic C, N, and P do not appear to influence the diversity of the genus of fungi.